Investigation into the carrier distribution and energy-band profile in AlGaN/GaN heterostructures with a graded AlGaN buffer. (19th October 2018) - Han, Tiecheng; Zhao, Hongdong; Han, Liying; Peng, Xiaocan; Li, Yuhai
Abstract: In GaN-based high-electron mobility transistors, although excellent electron confinement has been demonstrated using a graded AlGaN buffer with linearly decreasing Al-content along [0001] direction, guidelines for graded buffer design are still lacking. To obtain overall pictures of the carrier distribution and energy-band profile in AlGaN/GaN/graded AlGaN buffer heterostructures, the influences of the related physical parameters of the buffer are studied by one-dimensional self-consistent simulation. The results show that the negative polarization charge over the buffer can induce free holes in the depths of the buffer, resulting in the coexistence of electrons and holes. By adjusting the related physical parameters of the buffer, it is even possible to form two-dimensional holes gas (2DHG) at the channel/graded buffer interface. The cause of the coexistence of electrons and holes and the formation condition of 2DHG are analyzed. In addition, in the course of the variation of the related physical parameters, the characteristics of the two-dimensional electron gas density are also exhibited. This study can provide a reference for graded AlGaN buffer design in GaN-based field-effect transistors.